Kidnapped: An Adventure Classic - Francis, Pauline (Evans Brother Ltd, 2002)
A newly orphaned young boy who is cheated out of his inheritance by his uncle and kidnapped. Then, amid the conflict between the Jacobites and the supporters of King George II, David is fasely accused of murder and must flee for his life!
Keywords: Juvenile Fiction / Adventure